Optimizing the treatment of dental caries with laser Er Cr: YSGG 2,790 nm (WaterLase Biolase USA) - Dana Andreea Tudose; Cornelia Biclesanu (Amaltea Medical Publishing House, 2020)
Introduction. The increase in the prevalence of dental caries associated with the anxiety reaction of patients for the dental office have led to the emergence of modern, non-invasive and painless methods for the treatment of dental caries. The dental laser is one of these solutions. Case presentation. The 27-year-old patient presented multiple simple untreated medium and deep cervical carious lesions at 2.2, 3.3, 4.3, marginal secondary caries at 1.1, 2.1, root debris 3.6,4.6. The patient's age and increased carious activity were a reason for instituting a treatment as minimally invasive as possible, while maintaining as much dental vitality as possible and performing reconstructions that can be easily corrected and monitored. We opted for the treatment of caries with Er Cr: YSGG laser (erbium, chrome: yttrium - scandium - gallium - garnet) 2,790 nm and restoration with composite materials and direct restoration techniques. In this way, aesthetic and resistant restorations were obtained which have the advantages related to the performance of the laser working technique, such as increasing the resistance of the dental structures to acid attack and eliminating the risk of secondary caries. Although the duration of the sessions was longer, the patient accepted this solution to overcome her fear of the dental office. Conclusions. Er Cr: YSGG 2,790 nm laser is a viable alternative for the surgical stage of dental caries treatment ensuring a tissue substrate more resistant to secondary caries and being much more easily tolerated by patients.